TRANSFORMATIONAND POLICY PROBLEMS ISLAMIC EDUCATION - M. Kasyful Anwar; Sabran; Sri Susmiati (Jurnal Tarbiyatuna: Jurnal Kajian Pendidikan, Pemikiran dan Pengembangan Pendidikan Islam, 2026)
This study examines the dynamics and challenges in the implementation of Islamic education  policies across various levels of education in Indonesia, ranging from primary education to  higher education. Using a descriptive qualitative approach, the study analyzes how these  policies contribute to national education goals and address structural issues within the  education system. The findings reveal that despite the existence of systematic regulations,  significant challenges remain, including the uneven distribution and quality of educators,  disparities in facilities between urban and rural areas, unstable curricula, and weak institutional  coordination. These issues are further exacerbated by limited professional training  opportunities and inadequate integration of Islamic values and religious moderation. The  authors propose several solutions, including the digitalization of Islamic education,  strengthening teacher competencies, implementing context-based curriculum reforms, and  enhancing community engagement. The study highlights the importance of participatory and  locally responsive policy reforms to improve the quality and relevance of Islamic education in  Indonesia. The implications of this study suggest that adaptive and sustainable policy  implementation can enhance the quality of Islamic education, promote equitable access to  educational opportunities, and support the development of competent, moderate, and character driven learners in accordance with the goals of national education. The implication of implementing these policy recommendations has the potential to improve the quality of learning processes and outcomes, expand access to more equitable Islamic education, reduce the gap in education quality between regions, and strengthen the pedagogical and professional strength of teachers.